Sorption of Metal Ions on a Mixed Oxide [0.5 M SiO:0.5 M Fe(OH)] - S. Mustafa; B. Dilara; A. Naeem; N. Rahana; P. Shahida (Adsorption Science & Technology)
The sorption of Zn 2+ , Ni 2+ , Cd 2+ , Ca 2+ and Mg 2+ ions on to a mixed oxide of iron and silicon was found to increase with increasing temperature, concentration and pH of the system. The selectivity of this mixed oxide was Cd 2+ ≥ Zn 2 + ≥ Ni 2+ > Ca 2+ > Mg 2+ , indicating that the mixed oxide was more selective as an exchanger towards Cd 2+ ions relative to its components, SiO 2 and Fe(OH) 3 . The sorption data fitted the linear forms of the Kurbatov and Langmuir adsorption equations. The sorption of metal cations was accompanied by the release of H + ions to the bulk phase. On average 1 mol H + was released for every cation sorbed. The values of the binding constants were used to estimate the apparent thermodynamic parameters, ΔH and ΔS. The phenomenon of enthalpy/entropy compensation showed that the adsorption of metal ions by the mixed oxide occurred typically through a cation-exchange mechanism.